PERSPECTIVES OF SOCIAL ASPECTS OF SUSTAINABLE DEVELOPMENT IN THE LATVIA’S REGION LATGALE - Makarevičs, Valērijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
For the conception of sustainable development the elaboration of indicators allowing to determine its tendencies is of major importance. The practice shows that the lists of sustainable development criteria suggested at present do not take into consideration the pecularities of particular regions. Modern theories of sustainable development consider this phenomenon in three aspects: economic, ecological and social. The article considers the tendencies of sustainable development in the social sphere in Latgale in comparison to other regions of Latvia. The indicator here is the condition and possibilities of development of human capital (decent life for generations). The method of the research is the analysis of the statistical data. The conclusion is made on the basis of the research that the situation in the social sphere of Latgale does not correspond to the requirements of sustainable development. Research has two aims: to check the criteria of sustainbility development often mentioned in scientific literature in relation to Latvia; research of social aspect of sustainable development of east region of Latvia.